PEMBENTUKAN KARAKTER RELIGIUS SISWA MELALUI PROGRAM MEMBACA AL – QUR’AN DAN SHOLAT DHUHA DI UPT SD NEGERI 71 GRESIK - Khulailah Khulailah; Ismail Marzuki (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
Religious character is one of the character values ​​related to God, religious character is the main point that needs to be instilled and developed in children from an early age to become the basis of religious teachings in individual and social life, so as to foster one's behavior in accordance with the Al-Qur'an, as guidelines and demands of life of Muslims. This study aims to determine the formation of students' religious character through the Al-Qur'an reading program and Duha prayer at UPT SD Negeri 71 Gresik. This study uses a type of qualitative research. Data collection techniques namely observation, interviews and documentation. Sources of data were obtained through interviews with school principals, teachers and students. The results of this study indicate that there are implications of the Al-Qur'an reading program and Duha prayer in forming religious character in students which are shown, by increasing the ability to read the Al-Qur'an, increasing awareness in worship, discipline and responsibility, honesty , and form good morals, attitudes and manners. With this activity, it is hoped that it will provide motivation and enthusiasm for students to increase their memorization in reading the Qur'an, not only reading the Qur'an and memorizing it, but being able to interpret the holy verses of the Qur'an and practice it in social life, increasing their worship can be distinguishing noble moral values ​​and despicable morals and becoming good habits that are difficult to abandon in the future.